(untitled) (Papeles, 2010)
Following article aims to review current regulations on the emotional training in early childhood education in Colombia. The paper reviews the 1991 Constitution, relevant laws and decrees and National Education Plans. Intentionally not included district public policy, because the focus is on national provisions. The analysis presented are part of the partial results of the research project Social control of emotions in early childhood education in Bogota: Four cases, funded by the Antonio Nariño University in 2010. This work may serve as input to all those educational institutions interested in implementing emotional training in Early Childhood Education based on national legislation.